2007
DOI: 10.1111/j.1572-0241.2006.00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Outcome, and Prognosis in 273 Patients with Primary Sclerosing Cholangitis: A Single Center Study

Abstract: A persistent bilirubin elevation for longer than 3 months from the time of diagnosis could be identified as a novel marker correlating with a poor outcome. A new prognostic model was developed to predict progression of PSC, which may be useful in timing of liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 348 publications
(180 citation statements)
references
References 26 publications
10
163
3
1
Order By: Relevance
“…Also, previous studies have revealed that bacteriobilia and fungibilia seem to influence the outcome of PSC in a negative way. 5,12,42 This observation was partly confirmed by our data. However, our data were not significant for Candida spp., which may be due to the small number of only 11 PSC patients with the presence of Candida in bile in our cohort.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, previous studies have revealed that bacteriobilia and fungibilia seem to influence the outcome of PSC in a negative way. 5,12,42 This observation was partly confirmed by our data. However, our data were not significant for Candida spp., which may be due to the small number of only 11 PSC patients with the presence of Candida in bile in our cohort.…”
Section: Discussionsupporting
confidence: 90%
“…57 As yet, the only cure for PSC remains liver transplantation, 8 mean transplantation-free survival ranging from 9.6 to 12 years. 912 This is why currently the right selection of patients for this therapy and their position on the waiting list are of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Median transplant‐free survival from time of PSC diagnosis is variable, ranging from approximately 12‐21 years in most studies, with more recent estimates being toward the top end of this range 4, 5, 6, 7, 8. It has been reported that 40%‐58% of patients with PSC will develop focal high‐grade strictures, referred to as a “dominant stricture” (DS), during the course of disease 5, 9, 10, 11, 12. Patients with a DS may remain asymptomatic or may present with worsening serum liver tests, abdominal pain, and/or cholangitis 9.…”
mentioning
confidence: 99%
“…20 Similar studies demonstrated an incidence of cholangiocarcinoma of 13.2 % in a cohort of 273 German PSC patients followed for a median of 6.3 years and 6.8 % in 161 PSC patients followed for 11.5 years. 21,22 Furthermore, occult cholangiocarcinoma has been identified in up to 40 % of PSC patients at autopsy and between 9 and 36 % of liver explants after transplantation. 2326 The highest risk of cholangiocarcinoma has been shown within the first year after diagnosis of PSC, and careful screening and regular follow-up are recommended for patients who present with PSC for at least the first 2 years following diagnosis.…”
Section: Demographicsmentioning
confidence: 99%